Traceability in the Dairy Industry in Europe Theory and Practice - Mania, Ignazio; Delgado, Amélia Martins; Barone, Caterina; Parisi, Salvatore; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book explores food traceability in raw materials, additives and packing of the dairy sector and it provides an accessible and succinct overview of the new Extended Traceability (ExTra) software. In this work, the authors present several practical examples of extended food traceability for edible products and food-contact materials in the cheese-making industry. Readers will also discover a summary of the existing legal and regulatory requirements for food traceability in Europe. This book will appeal to a wide readership, from academic researchers to professionals and auditors in industry working in quality control, food and packing traceability, and international regulation. .
Food Traceability System in Europe: Basic and Regulatory Requirements -- Raw Materials in the Cheesemaking Field and Related Input Data in the Traceability -- The ExTra tool: a Practical Example of Extended Food Traceability for Cheese Productions -- The ExTra tool: Practical Simulations in the Cheesemaking Industry when using Cheeses, Butter, and Rennet Caseins -- The Legislative Status of Food Additives in the Cheesemaking Field: the European Perspective -- Food Additives in Cheese Substitutes -- Food Additives for Analogue Cheeses and Traceability: The "ExTra" Tool -- Food Packaging and the Mandatory Traceability in Europe -- Food Packaging Materials in the Cheesemaking Field -- The ExTra tool: Practical Simulations of Traceability for Cheese Packaging Materials.
Keywords: Food science; Nutrition .; Business logistics; Commercial law; Security systems; Food Science; Nutrition; Supply Chain Management; Commercial Law; Security Science and Technology